Calpain System in meat tenderization: A molecular approach - Coria, Maria Sumampa (2018)
Tenderness is considered the most important meat quality trait regarding its eating quality. Post mortem meat tenderization is primarily the result of calpain mediated degradation of key proteins within muscles fibers. The calpain system originally comprised three molecules: two Ca2+-dependent proteases and a specific inhibitor. Numerous studies have shown that the calpain system plays a central role in postmortem proteolysis and meat tenderization. The objective of this review is to describe the last biochemical and molecular findings in connection with this proteolytic system and their relation with meat tenderness in bovine. Findings of DNA polymorphisms and mRNA and protein expression are described as tools to predict meat tenderness. Understanding the molecular basis of meat tenderization may be useful particularly to the meat industry and may allow amendment of pre-slaughter handling practices and postmortem treatments that improves meat quality.